2016
DOI: 10.1021/acscatal.6b01719
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Efficient Palladium Catalysts for Electroreduction of Carbon Dioxide to Formate

Abstract: The electrochemical reduction of CO 2 into renewable chemical products such as formic acid is an important and challenging goal. Traditional Pd catalysts suffer from CO poisoning, which leads to current density decay and short operating lifetimes. Here we explored the ability to control Pd nanoparticle surface morphology to amplify catalytic activity and increase stability in the electroreduction of CO 2 to formate. Through computational studies we have elucidated trends in intermediate binding which govern th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
247
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 305 publications
(256 citation statements)
references
References 31 publications
8
247
1
Order By: Relevance
“…It has been shown previously that sharp tips can improve bubble nucleation, concentrate stabilizing cations and exhibit high local fields, all of which increase current densities [27][28][29][30] . This high current density also promotes high local pH, limiting the protonation of bound CO that leads to methane formation 54 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown previously that sharp tips can improve bubble nucleation, concentrate stabilizing cations and exhibit high local fields, all of which increase current densities [27][28][29][30] . This high current density also promotes high local pH, limiting the protonation of bound CO that leads to methane formation 54 .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, high-curvature structures, such as nanoneedles, promote nucleation of smaller gas bubbles 27 , and benefit from field-induced reagent concentration [28][29][30][31][32] , where high local negative electric fields concentrate positively charged cations to help stabilize CO 2 reduction intermediates 33 , enhancing CO 2 RR. However, combining high-curvature morphology with Cu + promotion to enable selective chemical conversion has yet to be explored.…”
Section: Articlesmentioning
confidence: 99%
“…The selectivity of CO 2 electroreduction also strongly depends on the concentration of the electrolyte . Taking Pd metal as an example, its main product of CO 2 electroreduction can be altered from CO to formate with an FE over 90%, by increasing the concentration of KHCO 3 solution from 0.1 to 0.5 m . As the absorbed hydrogen atoms are involved with the formation of CO and formate on Pd catalysts, a higher supply of hydrogen atoms by the relatively concentrated HCO 3 − leads to an enhanced hydrogen adsorption at the electrode/electrolyte interface, thus making formate the exclusive product in 0.5 m KHCO 3 solution …”
Section: Option Of Electrolytesmentioning
confidence: 99%
“…This can be explained by the roughest and active‐site‐abundant nature of Ag(110) among these three facets, which provides the highest catalytic activity in the CO 2 reduction reaction. For Pd metals, the activity of CO 2 electroreduction is in the sequence of Pd(110) > Pd(111) > Pd(100) . Klinkova et al carried out density functional theory (DFT) studies of Pd(111), Pd(110), Pd(100), Pd(211) nanoparticles and a Pd 19 cluster to reveal the correlation between the surface atomic coordination and catalytic performance of CO 2 reduction .…”
Section: Design Of Electrocatalystsmentioning
confidence: 99%
“…[27] However, minor production of CO still inhibitst he CO 2 reduction and deactivates the electrode over time. [28] The present work introduces af acile and efficient methodf or the preparation of Pd nanoparticle films Palladium nanoparticles are effective for catalytic CO 2 reduction. [26] Very recently,S argent and co-workers found that the surfacem orphologyo fP dn anoparticles could highly affect the selectivity; ah igh-index surfacei mproved the stability for formate formation without the production of CO in aC O 2 electroreduction performed for 1h.…”
Section: Introductionmentioning
confidence: 99%